1997
DOI: 10.1038/ng0297-186
|View full text |Cite
|
Sign up to set email alerts
|

A novel mutation in the potassium channel gene KVLQT1 causes the Jervell and Lange-Nielsen cardioauditory syndrome

Abstract: The Jervell and Lange-Nielsen (JLN) syndrome (MIM 220400) is an inherited autosomal recessive disease characterized by a congenital bilateral deafness associated with a QT prolongation on the electrocardiogram, syncopal attacks due to ventricular arrhythmias and a high risk of sudden death. JLN syndrome is a rare disease, which seems to affect less than one percent of all deaf children. Linkage to chromosome 11p15.5 markers was found by analysing four consanguinous families. Recombinants allowed us to map the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
503
1
11

Year Published

1998
1998
2015
2015

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 812 publications
(530 citation statements)
references
References 26 publications
6
503
1
11
Order By: Relevance
“…Mutations in KCNQ1 cause the autosomal recessive Jervell and Lange‐Nielsen syndrome [MIM 220400], characterized by SNHL and cardiac abnormalities (long QT syndrome) (Jervell and Lange‐Nielsen, 1957; Neyroud et al, 1997). In this syndrome, there is an impaired K + secretion into the endolymph by the KCNQ1/KCNE1 channel complex on the apical membranes of the marginal cells in the stria vascularis, as confirmed in a mouse model with the homozygous mutants being completely deaf (Lee et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Mutations in KCNQ1 cause the autosomal recessive Jervell and Lange‐Nielsen syndrome [MIM 220400], characterized by SNHL and cardiac abnormalities (long QT syndrome) (Jervell and Lange‐Nielsen, 1957; Neyroud et al, 1997). In this syndrome, there is an impaired K + secretion into the endolymph by the KCNQ1/KCNE1 channel complex on the apical membranes of the marginal cells in the stria vascularis, as confirmed in a mouse model with the homozygous mutants being completely deaf (Lee et al, 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Previous studies reported that KCNQ1 mutations were associated with long QT syndrome [8] and familial atrial fibrillation [9]. GWA scans have recently linked KCNQ1 to susceptibility to type 2 diabetes in a Japanese population [2,3].…”
Section: Discussionmentioning
confidence: 99%
“…Isk encodes a transmembrane protein that assembles with potassium channel subunits including Kcnq1. Mutations in both KCNQ1 and KCNE1 cause Jervell and Lange-Nielsen syndrome in humans (Neyroud et al 1997;Schulze-Bahr et al 1997), a syndrome associated with ventricular tachyarrhythmias of the heart and deafness. Knockout mouse models for both genes show a collapsed membranous labyrinth indicative of endolymph secretion failure and disruption of fluid homeostasis in the inner ear (Vetter et al 1996;Lee et al 2000;Casimiro et al 2001).…”
Section: Genes That Affect Fluid Homeostasismentioning
confidence: 99%
“…Kcnq1(Kvlqt1) or isk (KCNE1) are both expressed in the marginal cells of the stria (Sakagami et al 1991;Wangemann et al 1995;Neyroud et al 1997). Kcnq1 encodes a potassium channel subunit in the same family as Kcnq4.…”
Section: Genes That Affect Fluid Homeostasismentioning
confidence: 99%